Systematic literature review and meta-analysis on the reproductive effects of micro- pollutants in humans and animals - Coppeta, Luca; Ferrari, Cristiana; Ippoliti, Lorenzo; Campagnolo, Luisa; Magrini, Andrea (Frontiers in Toxicology, 2025)
BackgroundMicro-pollutants, such as particulate matter, heavy metals, endocrine-disrupting compounds, and persistent organic pollutants, raise significant concerns regarding reproductive health in both humans and animals.MethodsThis systematic review and meta-analysis, conducted according to PRISMA guidelines, assessed available evidence on micro-pollutant exposure and reproductive outcomes. Out of 2,134 records identified, 52 studies (31 human, 21 animal) met inclusion criteria.ResultsExposure to micro-pollutants was consistently associated with adverse reproductive outcomes. Human studies reported increased risks of irregular menstruation, preterm delivery (OR = 1.42), intrauterine growth restriction (OR = 1.36), and reductions in sperm concentration (SMD = −0.48) and testosterone levels. A meta-analysis of 23 studies confirmed these associations, while animal studies provided mechanistic support, including histological damage and epigenetic modifications. Despite substantial heterogeneity, the overall quality of included studies was moderate-to-high.ConclusionEvidence indicates that micro-pollutants are strongly associated with impaired reproductive health. While causality cannot be definitively established due to observational study designs, the consistency of findings across populations, pollutants, and species highlights an urgent need for further research and regulatory measures to mitigate reproductive risks.